Pharmacokinetics and Bioequivalence of Two Ibuprofen Sustained-Release Formulations after Single and Multiple Doses in Healthy Chinese Male Volunteers - Luo, L.-F.; Tian, Y.; Guo, H.-M.; Li, G.; Zhang, Z.-J. (Drug Research, 2013)
The aim of this study was to compare the bioavailability of 2 ibuprofen sustained-release formulations after single and multiple doses.It was conducted on 19 healthy Chinese male volunteers according to an open, randomized, single-blind, 2-way crossover study. Plasma concentrations were determined by liquid chromatography-mass spectrometry. Pharmacokinetic parameters were calculated using a non-compartment model.In the single-dose study, the values of Cmax, tmax, t1/2, AUC0–τ, AUC0–∞ for test and reference formulations were 12.59±2.29 and 12.84±2.79 μg/mL, 4.5±1.1 and 4.3±0.7 h, 4.15±1.37 and 4.03±0.86 h, 83.71±21.01 and 86.32±23.42 μg · h/mL, 86.05±21.37 and 88.99±25.33 μg · h/mL, respectively. In the multiple-dose study, the values of Cmax, Cmin, tmax, t1/2, AUCss, DF for test and reference formulations were 14.46±3.08 and 14.00±2.61 μg/mL, 0.47±0.21 and 0.63±0.45 μg/mL, 4.0±0.9 and 4.3±0.9 h, 4.69±1.61 and 4.99±2.16 h, 89.11±19.04 and 89.23±20.56 μg · h/mL, 3.25±0.50 and 3.06±0.71, respectively. Single-dose relative bioavailability were 97.8±10.5% for AUC0–τ and multiple-dose relative bioavailability were 100.6±9.4% for AUCss. The 90% confidence intervals of the T/R-ratios of logarithmically transformed data were in the generally accepted range of 80–125%.This means that the test formulation is bioequivalent to the reference formulation.
Keywords: ibuprofen; bioequivalence; pharmacokinetics; LC-MS; Chinese volunteers